ANALISIS PENGARUH CURRENT RATIO, DEBT TO TOTAL ASSET RATIO, TOTAL ASSET TURNOVER, DAN SALES GROWTH RATIO TERHADAP KONDISI FINANCIAL DISTRESS (Studi Kasus Pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2012-2014) - Yudiawati, Rike; Indriani, Astiwi (Faculty of Economics and Business Diponegoro University, 2016)
This research aimed to analyze the effect of current ratio, debt to total asset ratio, totalasset turnover, and sales growth ratio to financial distress condition in manufactur firms listed inIndonesia Stock Exchange for the period 2012-2014. The population in this research are all of the manufactur firms sector listed in Indonesia Stock Exchange that published financial statement in the year 2012-2014. Samples that obtained by purposive sampling are 95 firms and there are 285 observation data which consist of Â 66 financial distress and 219 non financial distress samples. The criteria of financial distress is measured by interest coverage ratio. The statistic analysis that used in this research was logistic regression. The result of this research showed that debt to total asset ratio, total asset turnover, and sales growth ratio have negatif and significant impact to financial distress. On the other hand, this research showed that current ratio have a significant impact to financial distress, with positive direction.